Future developments in neurovascular ultrasound - Meairs, Stephen; Hennerici, Michael G. (Handbook on neurovascular ultrasound, 2006)
Significant new developments in neurovascular ultrasound include molecular approaches to diagnostics and therapy. Addition of targeted ligands to microbubbles, has opened new avenues for the identification of vascular injury. This is because the molecular signatures of overexpressed adhesion molecules such as the integrin alphavbeta3, ICAM-1, and fibrinogen receptor GPIIb/II can be used to localize contrast agents through the use of complementary receptor ligands. Recent experiments have demonstrated the feasibility of microbubble-ultrasound-enhanced gene therapy to the brain. This new technology holds the promise of delivering genes more selectively than other methods and less invasively than direct injection. Microbubbles may also be employed as carriers of gene agents. The ability to focus ultrasound and cause local cavitation with these carriers may provide a new tool for gene therapy. Fortuitously, the intact blood-brain barrier (BBB), a major limitation in using genes for therapy of brain disease, can be opened with ultrasound. This localized, transient, and reversible opening of the BBB with ultrasound can provide an anatomically selective and targeted gene delivery. Future developments in neurovascular ultrasound will include improvements in technologies for ligand attachment to microbubbles, better methods for imaging targeted ultrasound agents in the brain, and optimization of ultrasound-mediated gene delivery.
Gesehen am 05.05.2022